Effect of the helicity injection rate and the Lundquist number on spheromak sustainment - Garcia Martinez, Pablo Luis (2014)
The dynamics of the magnetic relaxation process during the sustainment of spheromak configurations at different helicity injection rates is studied. The three-dimensional activity is recovered using time-dependent resistive magnetohydrodynamic simulations. A cylindrical flux conserver with concentric electrodes is used to model configurations driven by a magnetized coaxial gun. Magnetic helicity is injected by tangential boundary flows. Different regimes of sustainment are identified and characterized in terms of the safety factor profile. The spatial and temporal behavior of fluctuations is described. The dynamo action is shown to be in close agreement with existing experimental data. These results are relevant to the design and operation of helicity injected devices, as well as to basic understanding of the plasma relaxation mechanism in quasi-steady state.